The Effects of Exenatide Once Weekly (EXQW) and Exenatide Twice a Day (EXBID) on Beta-Cell Function in Type 2 Diabetes: A Systematic Review and Network Meta-Analysis. (28th October 2019) - Wang, Jie; Jin, Xinye; An, Ping; Yu, Songyan; Mu, Yiming
Abstract : Background . In patients with type 2 diabetes mellitus (T2DM) and poor glycemic control receiving metformin (MET), glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are recommended as the adjunctive therapy. However, there are only a few studies involving the comparative effects of exenatide twice a day (EXBID) and exenatide once weekly (EXQW) on HOMA- β . This meta assessed the comparative effects of EXQW and EXBID on HOMA- β among T2DM patients. Materials and Methods . PubMed, Cochrane Library, and Embase databases were searched to collect randomized controlled trials (RCTs). Network meta-analysis was performed, and network diagrams were constructed to evaluate the effects. The primary outcome is HOMA- β, and the secondary outcomes are fasting blood glycose (FBG), glycated hemoglobin (HbA1c), and weight loss. Results . A total of 8 studies with 3506 subjects were included. Compared with other antidiabetic agents, EXQW has a greater improvement in HOMA- β than EXBID (weight   mean   difference   WMD = ‐ 0.46, 95% confidence interval (CI) [-0.64, -0.28], P = 0.001 ). The effect of EXQW on HbA1c is superior to that of sitagliptin (SITA) (WMD = 0.51, 95% CI [0.03, 0.99], P = 0.037 ). The significant reduction of weight was detected for EXBID in comparison with EXQW (WMD = ‐ 0.73, 95% CI [-1.13, -0.33], P = 0.001 ), and no significant difference was found between EXQW and MET. Conclusions . EXQW shows a greater improvement in HOMA- β than EXBID. Moreover, the efficacy of EXQW on glycemic control is similar to other antidiabetic agents including EXBID. It is an advisable treatment for diabetic patients to improve HOMA- β and has an advantage of fewer number of injections compared with EXBID, to increase patients' adherence and quality of life.